Granzyme A in Chikungunya and Other Arboviral Infections - Schanoski, Alessandra S.; Le, Thuy T.; Kaiserman, Dion; Rowe, Caitlin; Prow, Natalie A.; Barboza, Diego D.; Santos, Cliomar A.; Zanotto, Paolo M. A.; Magalhães, Kelly G.; Aurelio, Luigi; Muller, David; Young, Paul; et al. (Frontiers in Immunology, 2020)
Granzyme A (GzmA) is secreted by cytotoxic lymphocytes and has traditionally been viewed as a mediator of cell death, although a growing body of data suggests its physiological role if promotion of inflammation. Herein we show that GzmA is significantly elevated in the serum of chikungunya virus (CHIKV) patients and that levels correlated with viral load and disease scores. CHIKV mouse models showed circulating GzmA is largely derived from NK cells, with no evidence for GzmA expression by CD4 T cells. Infection of mice deficient in type I interferon responses with CHIKV, Zika virus and dengue virus resulted in high levels of GzmA. We also show herein that rmGzmA is alone and sufficient to mediate inflammation and that this activity requires the protease to be enzymatically active.